Strategic systems planning for financial institutions : using automated solutions and technology for competitive advantages - Wold, Geoffrey H.; Shriver, Robert F. (Chicago, Ill. : Probus Pub. ; Cambridge, England : Bankers Pub., 1993)
Strategic systems planning for financial institutions, describes a methodology for developing a strategic information systems plan to guide the effective management of information resources.
Includes bibliographical references (p. [295]-297) and index.
rpm 08/09/2016
Loans
Keywords: Financial institutions; Information resources management; Financial institutions -- management -- data processing; System analysis